Knowledge collecting and donating in public service innovation at Hasanuddin University - M NATSIR; Sangkala Sangkala; Muhammad Yunus (The International Journal of Politics and Sociology Research, 2023)
The urgency of research on the effect of knowledge collecting and donating on innovative work behavior is due to the fact that innovative work behaviors play an important role in employee innovation in organizations. This study aims to examine the effect of knowledge collecting and donating on innovative work behavior. Quantitative methods are used to test knowledge collecting and donating on innovative work behavior. The research location is at Hasanuddin University, Makassar City. The population in this study were all employees at the Hasanuddin University Finance Bureau with status as state civil servants. Primary data collection by distributing questionnaires. The data analysis technique uses multiple linear regression analysis. The research findings show that knowledge collecting and knowledge donating have a positive and significant effect both partially and simultaneously on innovative work behavior. The research contribution highlights the importance of knowledge collecting and knowledge donating in public service innovation to develop innovative work behavior. The limitation of this research is only to explore the subjective perceptions of innovating work behavior. Research originality, there is no comprehensive research that assesses knowledge collecting and donating on innovative work behavior.